2015
DOI: 10.1177/1462474515604385
|View full text |Cite
|
Sign up to set email alerts
|

The structure of public opinion on crime policy: Evidence from seven Caribbean nations

Abstract: A long tradition of research has examined public opinion on crime policy. Much of this research focuses on identifying the determinants and correlates of public opinion; few studies have examined the dimensional structure of public attitudes toward crime policy. This study posits and tests a multidimensional conceptualization of attitudes toward crime policy. We hypothesize that two general dimensions -punitiveness and progressiveness -are the minimum necessary to account for people's opinions on crime policy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 73 publications
1
10
0
1
Order By: Relevance
“…Recent research suggests that at least some portion of the public might hold these competing views, not only in regard to front-end processes like crime control and sentencing (Maguire and Johnson, 2015), but also at the back-end in relation to prisoner release. Based on a US sample, O’Hear and Wheelock (2015) found a distinctive subgroup of members of the public who are supportive of both early supervised release from prison (i.e.…”
Section: Heterogeneity In Public Attitudes Towards Parolementioning
confidence: 99%
“…Recent research suggests that at least some portion of the public might hold these competing views, not only in regard to front-end processes like crime control and sentencing (Maguire and Johnson, 2015), but also at the back-end in relation to prisoner release. Based on a US sample, O’Hear and Wheelock (2015) found a distinctive subgroup of members of the public who are supportive of both early supervised release from prison (i.e.…”
Section: Heterogeneity In Public Attitudes Towards Parolementioning
confidence: 99%
“…In light of the statistics on crime in Barbados, it might seem that this diagnosis was misplaced. Maguire and Johnson (2015: 251) reference the ‘placid island of Barbados’ in their study. There was awareness of crime in Barbados as low relative to other countries, for instance, Regina’s admission that: ‘I generally feel that Barbados is a much more safer place than where I come from [another Caribbean nation]’.…”
Section: Resultsmentioning
confidence: 99%
“…The little research that does exist is quantitative, and does not explore the deeper meanings of these matters for people in Barbados. A 2010 survey suggested that Barbados was less punitive than its Caribbean peers (Maguire and Johnson, 2015). Surveys from 1999, 2004 and 2010 measured public opinion on capital punishment and asked respondents to indicate whether they 'Support the Death Penalty', 'Don't Support the Death Penalty' or 'Don't Know'.…”
Section: Researching Populist Punitiveness In the Caribbeanmentioning
confidence: 99%
“…According to Maguire and Johnson (2015, p. 507), punitive policies are “policies intended to punish offenders for their misdeeds.” In contrast, progressive policies are “prevention policies that address the ‘root causes’ of crime, as well as rehabilitative and re-entry programs that aim to reduce recidivism and reintegrate offenders into society” (p. 508). Thus, for the purposes of the present study, punitive policies refer to crime prevention strategies that appear designed to punish individuals who commit crime or that fail to address the underlying causes of crime.…”
Section: Literature Reviewmentioning
confidence: 99%